Types of Morning-Evening Personality and its Relationship with Self-Vitality and Procrastination Behavior among University Students - Suleiman Khatatbeh, Yahya Mubark; Abdullah Fareh Miri, El-Walid Bin (International Journal of Psychosocial Rehabilitation, 2021)
The present study has aimed at revealing the connection between the types of morning-eveningpersonality and its relationship with the university students’ self-vitality and procrastination. It hasalso aimed at finding out the differences in the morning-evening personality, self-vitality andprocrastination as per the demographic variables (gender, age, academic average, academicspecialization and physical illnesses). The sample of the study consisted of a number of 691 students(males and females). For achieving the objectives of the study, the following tools have been used:scale of morning-evening personality developed by Biggs (2015), Ryan & Fredrch’s self-vitality scale(1997) and Kiser’s procrastination scale (2020).The result of the study indicated that the university students’ dominating personality type isrepresented by the moderate type between the morning personality and the evening one, the averageprocrastination level and the high level of self-vitality. It was also found that there are differences inthe levels of self-vitality and procrastination for females in comparison with males, for sickindividuals in comparison with those suffered from illness in the past, for those whose ages rangefrom 19 to 22 in comparison with other age groups, the less self-vitality of those in humanitiesspecializations in comparison with other specializations. Moreover, those in forensic specializationswere much tendentious to procrastination than the students in other specializations. As per theacademic average variable, the differences in self-vitality were in favor of those who got (VeryGood). Such differences were in favor of those who got (Good) as per the procrastination variable.Besides, the differences were in favor of those who belong to the evening personality in comparisonwith other groups concerning the variables of self-vitality and procrastination. The results made itclear that the self-vitality has a statistical significant role in explicating the types of personality(13%), while procrastination recorded a difference of 12 percent.